Sistem Informasi Pelayanan Medis Pada Pasien di Klinik Insani Citeureup Berbasis Java - Rina Deviana Alit; Meri Chrismes Aruan; Andri Rahadyan (Informatika Universitas Siliwangi, 2020)
The purpose of this research is to design a medical service information system for Java-based human citeureup clinical patients to accelerate and manage patient data, search for medical service information systems and to produce medical service information systems in Java-based human clinical clinics. The research method used by researchers is a qualitative research method that is research on research conducted descriptive and using analysis. The results obtained were about medical service information systems to assist in processing patient data. The construction of this information system is expected to facilitate and provide maximum service to patients as well as facilitate the processing of transaction data for reporting, data and information management processes become more effective, produce faster output and no longer use incorrect data input or require duplication of data.